2018
DOI: 10.21101/cejph.a5090
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ADH1B genotypes predisposed to enhanced alcohol consumption in the Czech Roma/Gypsy population

Abstract: Objective: The aim of the study was to analyse the frequencies of rs1229984 genotypes within the alcohol dehydrogenase (ADH1B) gene in a Gypsies/Roma population and compare them with other populations and with ethanol consumption. Methods: We analysed the ADH1B (rs1229984; Arg47→His; c.143G>A) genotype using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) in two ethnically different groups-Gypsies/Roma (N = 301) and Czechs (N = 300) where one day alcohol consumption was record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Heterozygous (A/guanine [G]) and/or homozygous A/A carriers of the mutant allele from either SNP have increased rates of ethanol metabolism, reduced rates of alcohol consumption, and reduced risk of alcohol dependence and alcoholism [ 53 ]. This may all be due to increased levels of acetaldehyde and its associated subsequent adverse effects [ 53 , 54 , 55 ]. A variant in the rs1229984 SNP leads to the substitution of the amino acid histidine for arginine at position 48 [ 53 ].…”
Section: Genetic Testing and Nutrigeneticsmentioning
confidence: 99%
“…Heterozygous (A/guanine [G]) and/or homozygous A/A carriers of the mutant allele from either SNP have increased rates of ethanol metabolism, reduced rates of alcohol consumption, and reduced risk of alcohol dependence and alcoholism [ 53 ]. This may all be due to increased levels of acetaldehyde and its associated subsequent adverse effects [ 53 , 54 , 55 ]. A variant in the rs1229984 SNP leads to the substitution of the amino acid histidine for arginine at position 48 [ 53 ].…”
Section: Genetic Testing and Nutrigeneticsmentioning
confidence: 99%
“…Another study analyzing the distribution and combined effect of alcohol metabolism and neurotransmitter gene polymorphisms in the general Hungarian and Roma populations found no over-representation of genetic alterations predisposing to alcohol dependence and lower genetic risk scores in the minority population [ 59 ]. Furthermore, Hubáček et al identified ADH1B rs1229984 genotype frequencies in the Czech Roma population corresponding with frequencies of North India/Central Asia [ 60 ]. On the other hand, alcohol consumption phenotypes in relation to taste preference-related genetic variants in Roma populations in comparison with majority populations have not been investigated before [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Snowball sampling (Hughes et al, 1995) has been used to the Czech Roma/ Gypsy subpopulation (N = 302) selection and quota sampling (Walter, 1989) for recruiting Czech Caucasians/Slavs (N = 298). All subjects were older than 18 years at the time of data and samples collection and theirs ethnicity was based on self-reported information (Adámková et al, 2015, Hubáček et al, 2018.…”
mentioning
confidence: 99%